The VideoM@t project: Engaging students on learning tricky topics in mathematics through creative skills - Cruz, Sara (2018)
VideoM@ is the title of a communication presented at CSEDU 2018. VideoM@t is a project that focuses on helping students understanding threshold concepts in mathematics with the help of technological tools and collaborative high-level reflections.